Senescence-Induced Chemoresistance in Triple Negative Breast Cancer and Evolution-Based Treatment Strategies - Chakrabarty, Anindita; Chakraborty, Shayantani; Bhattacharya, Ranjini; Chowdhury, Goutam (Frontiers in Oncology, 2021)
Triple negative breast cancer (TNBC), the only BC subtype that lacks targeted therapy, is typically treated with combination chemotherapies. Although, initially responsive to chemotherapies, TNBC cells frequently acquire drug resistance and emerge as recurrent, metastatic tumors. Resistance to chemotherapy can develop through many different mechanisms, including induction of a transient growth-arrested state, known as therapy-induced senescence (TIS). In this minireview, we will focus on chemoresistance in TNBC due to TIS. One of the hallmarks of senescent cells is a complex secretory phenotype, known as the senescence-associated secretory proteome (SASP). SASP allow the recruitment of immune cells to eliminate senescent cells responsible for maintaining tissue homeostasis and suppressing tumorigenesis. However, in cancer, particularly with TIS, senescent cells themselves as well as the SASP can cause cellular reprograming into a stem-like state resulting in the emergence of drug-resistant, aggressive clones, that eventually cause tumor relapse and metastasis. From an evolutionary perspective, cancer is driven by natural selection, where the fittest tumor cells survive and proliferate while the tumor microenvironment influences tumor cell fitness. As TIS seems to be an evolutionary beneficial adaptation for increasing the fitness of drug-challenged cancer cells, we will propose a few strategies to control them by using the principles of evolutionary biology. We hope that by appropriate therapeutic intervention, this seemingly detrimental cellular fate could be diverted in favour of TNBC patients.